Health Promotion Education and Psychologic Melalui Peer Group Anxiety Disorder Sebagai Pencegahan Gangguan Kecemasan Remaja - Muhammad Ali Faisal; Dian Rosadi; Winardi Budiwinarta; Agus Muhammad Ridwan; Ranindy Qadrinnisa; Aisha Saraswati (Pusat Riset dan Inovasi Nasional, 2024)
Adolescent are prone to experiencing anxiety (Anxiety disorder), namely a condition of anxiety for a short time and feeling restless in every activity for no apparent reason. Anxiety is the most common mental disorder problem among teenagers in Indonesia, namely 26.7%. Based on the results of the situation and needs analysis with partners, namely the Youth Counseling Information Center (PIK-R) SMAN 1 Gambut, there are still several work programs from PIK-R that are still not optimal. Based on the results of the analysis, a significant value of 0.000<0.05 was obtained, which means there is a positive or meaningful relationship between the pre-test and post-test scores. This shows an increase in knowledge of 28 respondents (96%) between before and after providing education related to anxiety disorders at SMAN 1 Gambut. It is hoped that this activity can contribute to increasing students' knowledge and skills in dealing with anxiety disorders.